All III‐arsenide low threshold InAs quantum dot lasers on InP(001) - Jinkwan Kwoen; Natália Morais; Wenbo Zhan; Satoshi Iwamoto; Yasuhiko Arakawa (Electronics Letters, 2023)
Abstract This study investigates the development of InAs quantum dot (QD) lasers on a InP(001) substrate, utilizing only III‐arsenide layers. This approach avoids the issues associated with the use of phosphorus compounds, which are evident in the crystal growth of conventional C/L‐band QD lasers, making the manufacturing process safer, simpler, and more cost‐effective. The threshold current density of the fabricated QD laser was 633 A/cm2, which is the lowest value for QD lasers in the 1.6‐µm wavelength region. This result suggests a high cost‐effectiveness and paves the way towards a large‐scale production technology for high‐performing C/L/U‐band QD lasers.